The Sage handbook of family business - Melin, Leif; Nordqvist, Mattias; Sharma, Pramodita ca. 20./21. Jh (SAGE, 2014)
Edited by the leading figures in the field, with contributions and editorial board support from the most prominent names in family business, this handbook reflects on the development and present status of the field in terms of applied theories, methods, chosen research issues and theoretical contributions